E-1: FLOUTED SUCCESSION LAWS - Tahir, Muhammad; Khalil, Faiza (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
The paper intends to present an overview of local laws in the field, which have been enacted to deal with the subject of inheritance. Hypothetically, due to insufficient law making, Muslims constituting a significant part of the population in Pakistan are compelled to seek remedy from the court of law for the issues arising during the course of distribution. The relevant laws are either obsolete or piecemeal, which could hardly accommodate such complications, like ascertaining the share of legal heirs, mode of distribution amongst them, and recompensing of liability present upon the deceased. If the law of inheritance which currently exists as ‘The Succession Act 1925’ is reconstructed encompassing all the details, it could curb volumes of civil and criminal both categories of litigations in the courts of first instance.